SPECTROPHOTOMETRIC DETERMINATION OF TOTAL PHENOLIC CONTENT FOR STANDARDIZATION OF VARIOUS PHYLLANTHUS SPECIES - Rakhi Khabiya, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aims at comparison of total phenolic content of ethanolic extract of various species of Phyllanthus available in Gujarat state by spectrophotometric method. Methods : The total phenolic content was determined quantitatively using the Folin Ciocalteu reagent, with Gallic acid as standard. Results: The total phenolic content in methanolic extract of various Phyllanthus species ranged from 41.801 to 87.542 mg/g of dry weight of extract, expressed as gallic acid equivalents. Phyllanthus urinaria was found to have highest phenolic content and Phyllanthus acidus was found to have lowest phenolic content . Conclusion: The total phenolic content will be helpful for developing new drugs and standardizing the various Phyllanthus species particularly morphological similar species. The presence of a high total phenolic content shows that the alcoholic extract of Phyllanthus may possess antioxidant properties, which could lead to a new field of research in the future.